Characterization and Antimicrobial Activity of Whey Edible Film Composite Enriched with Clove Essential Oil - Fahrullah; M. Ervandi; D. Rosyidi (Faculty of Animal Science, Bogor Agricultural University, 2021)
Antimicrobial edible films made from clove essential oil play a role in reducing, inhibiting, or slowing the growth of bacteria that may be existed in food packaging or packaging materials to extend the shelf life of packaged foods. This study aims to produce whey and clove oil films with film thickness, elongation, tensile strength, water vapor transmission rate, optical properties, antimicrobial properties of clove oil, and its inhibition against pathogenic microbes. The physical and antimicrobial characteristics of edible film were investigated using an experimental method in a completely randomized design with four treatments. The treatment used different concentrations of clove oil (C0: 0% clove essential oil, C1: 5% clove essential oil, C2: 10% clove essential oil, and C3: 15% clove essential oil). The percentage value of elongation and microbial inhibitory activity were significantly affected (p<0.01) by the concentration of clove essential oil. Based on all variables, 10% clove essential oil concentration is the best treatment with a thickness of 0.035 mm, elongation of 78%, tensile strength of 8.82 N, water vapor transmission rate of 7.80 g.mm-2.day-1, and inhibitions of E. coli and S. aureus resulted in high rates. The results conclude that the addition of clove essential oil has a promising potential to improve the antimicrobial properties of whey edible film composites. The use of clove essential oil at the level of 10% is the best treatment.